Evaluation of quality of life and pain in Temporomandibular Disorders (TMD) - Anamaria Siriani Oliveira (Universidade Estadual de Campinas, 2015)
Pain and quality of life assessment must have a multidimensional approach. This paper presents studies about the impacts that pain due to temporomandibular disorders can have in the patients' life.